Dekonstruksi Gender Perspektif Rasyid Ridha (Studi Analisis Ayat-Ayat Bias Gender Pada Kitab Tafsir Al-Manār) - Roswati Nurdin (IAIN Ambon, 2017)
The book of Tafsir al-Manar stems from the interpretation of the Qur'an lectures given by Muhammad Abduh al-Azhar University, Egypt, which lasted from 1899 until his death (1905). The lectures are always attended by Rashid Rida, Abduh's pupil, which each verse was delivered by her teacher on record in his mind. Then the records drawn up in the form of regular writing and submitted and known as Tafsir al-Manar. Rashid Rida using deconstruction theory in explaining the pattern of gender relations when interpreting the verses of gender bias. Deconstruction theory in general can be understood as a method of demolition to the reality that contains logic Binner opposition. Binary oppositions are two realities are seen face to face, opposed and have a different position. This paradigm explains the assumption of privilege and contempt girded subject to the object, as the second class. In giving his interpretation Rashid Rida decontracting logic method is to re-position women liking the Qur'anic text. Keywords: deconstruction, Rasyid Ridha, Tafsir al-Manār